Autonomic Dysfunction in Current Cigarette Smokers Assessed by Time Series Analysis of Heart Rate Variability - Ferdouse, Mehboba; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2014)
Background: Cigarette smoking is one of the strong contributors to the risk of development of cardiovascular diseases including coronary artery disease, stroke, sudden death, peripheral artery disease & aortic aneurysm. Objective: To assess HRV by time domain methods in healthy cigarette smokers. Methods: This cross sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from July 2011 to June 2012. 120 apparently healthy male current regular cigarette smokers (Group B) aged 20-55 years were enrolled in the study group.70 apparently healthy male non smoker subjects (Group A) were taken as control. Time domain measures of HRV were recorded by a RMS digital Polyrite. Statistical analysis was done by independent sample t test. Results: Resting Pulse, SBP, DBP, Mean heart rate was significantly higher (p<0.001) and Mean R-R interval, SDNN, RMSSD were significantly lower (p<0.001) in all smokers compared to control. Conclusion: Generalized reduced HRV & attenuated cardiac vagal modulation occur in apparently healthy cigarette smokers. DOI: http://dx.doi.org/10.3329/jbsp.v8i2.18659 Bangladesh Soc Physiol. 2013, December; 8(2): 84-88